İzmit körfezi geçişi ekonomik değerlendirilmesi - Cihan, Deniz (Fen Bilimleri Enstitüsü, 1995)
Bu çalışmada İzmit Körfezi Geçişinin Ekonomik Değerlendirmesi yapılmıştır. Değerlendirme için üç alternatif göz önüne alınmıştır. İkinci bölümde alternatiflerin seçiminde göz önüne alman güzergahlar, bu güzergahların mevcut durumları ve ulaşım özellikleri verilmiştir. Üçüncü bölümde alternatifler belirlenmiş, başlangıç ve bitiş noktalan, kilometre uzunlukları ve yolculuk süreleri açıklanmıştır. Dördüncü bölümde karayolu, arabalı vapur ve otoyol seçenekleri için trafik araştırması yapılmış ve 1994-2015 yıllan arası trafik değerleri tahmin edilmiştir. Arabalı vapur trafiği tahmini için storm yazılımı kullanılarak regresyon analizi yapılmıştır. Bu analiz sonucu talep denklemi elde edilerek istatistik sonuçlar incelenmiştir. Beşinci bölümde taşıt işletme maliyetleri ; araç mesafe maliyetleri, araç zaman maliyetleri, birleşik toplam (mesafe+zaman) maliyetler,arabalı vapur yolculuğu maliyetleri ve arabalı vapur yolculuğu zaman maliyetleri başlıklan altoda incelenmiştir. Altıncı Bölümde Edime-Kınalı Otoyolu ve Fatih Sultan Mehmet Köprüsü yapım maliyetlerinden faydalanılarak Anadolu Otoyolu Dilovası Ayrımı-Orhangazi (Körfez Köprüsü Dahil ) Projesinin otoyol ve köprü bölümlerine ait yapım maliyetleri hesaplanmıştır. Bu bölümde ayrıca Otoyol ve Köprü Bakım İşletme maliyetleri, Karayolu Bakım İşletme maliyetleri hesaplanmıştır. Yedinci Bölümde ağırlıklı ortalama maliyetler ile alternatiflere ait tüm taşıt işletme, bakım,yapım ve arabalı vapur maliyetleri hesaplanmıştır. Tüm maliyetler 1994 yılma indirgenerek % 12, % 15, ve % 20 iskonto oranlan altoda ekonomik değerlendirme yapılmıştır. Ekonomik değerlendirme için Fayda/Maliyet oram ve Net Bugünkü Değer metodlarından faydalanılmışür.

The 449 Km İstanbul-Bursa-îzmir Highway project has been priority in 1993. The project, which will be opened for international tender on a BOT (Built, Operate, Transfer ) basis includes the construction of a 3 km long bridge across Izmit Buy to create a "short-cut" between Istanbul and Bursa. îzmit Buy crossing will take part of most concentrated section which planning îstanbul-Bursa-îzmir Motorway. The purpose of this study is to compare the Anatolian Motorway, Dilovasi Offramp-Orhangazi (Gulf Bridge included) project with the present transportation routes using economical analysis sistems. İn the second chapter,lzmit Gulf crossing alignments is studied. In the third chapter, alternatives are determined with their origins and destinations, in accordance with the alignements given in the second chapter. The first alternative represents the highway crossing. Its origin is Harem (İstanbul) and its destination is Orhangazi (Bursa). Alternative 1 is 180 Km long. Although the second alternative represents boat crossing, its origin and its destination are the same as in Alternative 1. Thus,it takes into consideration the highway sections used for arriving and departing from ferry boat route. Alternative 2 is 85 Km long in highway and 4.7 miles long seaway. The third alternative represents the motorway crossing. It starts from the Çamlıca intersection on the 0-2 motorway (K15); and continuing through the motorway and bridge section will be built after the Anatolian Motorway Dilovasi intersection^ will reach Orhangazi. Alternative 3 is 94 Km long in total, with 91 Km long motorway and 3 Km long bridge. Average speed on highway is taken 80 km/hr for a car, 60 km/hr for a bus, 50 km/hr for a lorry and truck. Thus alternative 1 average travel time is calculated 135 X1U minutes for a car, 180 minutes for a bus and 216 minutes for a lorry and truck. Ferry boat travel time is found to one hour including loading, crossing and unloading times. Therefore alternative 2 travel time is calculated 124 minutes for a car, 145 minutes for a bus and 162 minutes for a lorry and truck. Average speed on motorway is taken 110 km/hr for a car, 80 km/hr for a bus and 75 km/hr for a lorry and truck. Finally alternative 3 travel time is calculated 51 minutes for a car, 71 minutes for a bus and 75 minutes for a lorry and truck. în order to use any of models of the transportation system it is necessary to have estimates of the various parameters of those models. In transportation planning it has been discovered that parameters which apply to one city or metropolitan area often do not apply to another, and therefore every time a planning activity is under taken in particular area a basis for estimating the model parameters for that area must be developed. The primary means for doing this is to obtain survey sample data on tha characteristics of that particular metropolitan area and its transportation system, and from these estimate those parameter values which best replicate the data. In the fourth chapter, traffic that use Alternative 1 and Alternative 2 routes is determined. To determine the traffic that goes around The Izmit Gulf, values are taken from the Traffic Information Book of 1993 and research study results are obtained between Gölcük and Karamürsel in 18-19 February 1993 for the traffic that goes around îzmit Gulf by highway Future traffic values are estimated by using Traffic increase coefficient. Traffic values crossing the İzmit Gulf by ferry boat between 1989 and 1993 were obtained from T.D.I Şehir Hatları Müdürlüğü. To increase the sample size for regression analysis and to consider the seosonal changes, annual traffic values were examined in four terms. After many regression analysis, statistically meaning full, with its coefficients sign in the right direction and with a high coefficient of correlation, a demand equation is found. Future ferry boat traffic is estimated using this equation. The forecast for 2015 means that the bridge would be working at capacity of increasing congestion and delays during most hours of the days of the year. For the traffic that will be generated after the motorway and bridge crossing two assumptions are put into use. First one is that the traffic that will be shifted from the highway to the motorway will be % 80 or % 90; the second one is that all of the ferryboat traffic will be shifted to the motorway. The existing ferryboat traffic would probably be entirely superseded by motorway traffic accross the bridges so that the vehicular ferries might be expected to cease operating. HV Reduced operating costs are usually the most directly measurable benefits resulting from new transport projects. The correct method of determining the reduction involves the "with and without" test whereby the present operating costs are compared with an estimate of what the cost would be without the new facility. In the fifth Chapter, vehicle operating costs are examined for vehicle distance costs and vehicle time cost of the highway and motorway options. Vehicle distance costs include cash payings for maintenance, tires, oil. and gasoline. Vehicle time costs include the price of the vehicle, driver fee, insurance and interest. Passenger time costs are also added to this. Distance costs are calculated by TL/Veh.Km, and time costs are calculated by TL/Veh.Hr. Then time costs are converted to TL/Veh.Km and total vehicle operating costs are found. Ferryboat trip cost of a passenger car in 1993 is calculated by examining Eskihisar-Topçular route operating costs between 1989 and 1993.This value is multiplied by the car equivalent of each vehicle type ; and ferryboat vehicle costs are found for bus, lorry and truck. Ferryboat trip is found for one hour including loading, crossing and unloading times.If this value is multiplied by vehicle time costs (TL/Veh.Km), ferryboat trip time cost is found for each vehicle type. In the sixth chapter, Motorway and bridge construction costs are calculated, taking into consideration Edirne-Kınalı motorway and Fatih Sultan Mehmet Bridge construction costs. Like the existing Fatih Sultan Mehmet Bridge, Izmit Gulf Crossing Bridge would be a suspension bridge. The bridge is to carry three lane dual carriageways. The 120 Km/h design speed adopted, the bridge and access roads could be designed and constructed within four years, and thus it coluld be opened to traffic by 1999. Motorway and Bridge maintenance operating costs are obtained, with the help of Bosphorus Bridges and Kinali-Mahmutbey Motorway section maintenance operating costs of year 1994. The bridge and the relevant section is under the responsibility of General Directorate of Highways, 17. Division. The costs calculated in the fifth chapter are for each vehicle type. On the other hand, future traffic estimations for Alternative 2 and Alternative 3 are not made for each vehicle type. But total annual traffic is calculated. For this reason in the seventh chapter, weighted average costs are determine with the help of costs calculated in the fifth and sixth chapters. Vehicle operating XV costs and maintenance costs are found for Alternative 1 ; ferryboat trip costs, time cost and vehicle operating costs for the 85 km long highway section for Alternative 2; motorway and bridge construction costs, vehicleoperating cost and maintenance operating costs are calculated for Alternative 3. Benefits of Alternative 3, compared Alternative 1 and 2 reduced to years 1994; Benefit/Cost ratio and Net Presenth Worth are calculated. The aim of the economic evaluation is to consider the economic effects resulting from the construction of a crossing of the îzmit Buy. While considering the results of the economic evaluation it should be borne in mind that the construction of crossing would influence land use, and thus could increase the further benefits. The benefits resulting from transport investment are usually derived from: reduced operating costs of equipment, lower cost of maintaining the infrastructure, time savings, saving in accident costs, environmental improvement and greater comfort and convenience and economic stimulation. Several difficulties are involved in the quantification in monetary terms of the economic benefits which may result from investment in the transport infrastructure. The first of these difficulties in that market prices are invariably lacking so that even when direct benefits accrue, their economic worth can be measurable only inderectly. Next many of the benefits themselves my accrue indirectly and then only after contingent investment has taken place in an altogether different field. The benefits which result from transport investment are usually realized over a long period so that their estimation must depend on long term prediction. Overriding these difficulties is the conceptual one that benefits are only measurable as such in relation to their alternatives. Benefits resulting from the general improvement of the transportation network fall into several categories. User benefits arise when the generalised costs of movement are reduced so that jouraes becomes either cheaper in money terms or shorter in time. Travellers may also benefit if the comfort and convenience of travel are improved, but with the present methods of cost benefit analiysis, these cannot be reliably quantified and have been omitted. The user benefits determined include some elements which, although not contributing directly to an increase in gross domestic product, do have a value to individual members of the community and contribute to their welfare. The benefits to xvi vehicle operators resulting from improvements in journey time or costs are also included. The economic evaluation for İzmit Buy Crossing is to asses the best ways of meeting future requirements for highway, ferryboat line and motorway alternatives. Bridge costruction year is taken as 1995. ît will be the dominant facility for vehicular traffic. This economical evaluation comprises years 1994-2015. All evaluations are made according to year 1994. 1993 values are converted to year 1994 using the coefficients of The Ministery of Public Works and Settlements. Average exchange rate of year 1994 is taken as 1 USS $=29.883 -TL. No account is taken here of the effect of changes of land use consequent upon the construction of the bridge which might improve the financial rate of return somewhat.
Economic evaluation of izmit buy crossing
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: Ekonomik analiz; Maliyet analizi; Ulaşım sistemleri; İzmit Körfezi; Economic analysis; Cost analysis; Transportation systems; İzmit Bay